Stimulasi Kemampuan Motorik Halus Anak Usia 4-5 Tahun Melalui Kegiatan Meronce Pompom Di TK Perwari 1 Kota Tasikmalaya - Welsa Agustin, Fini; Yusuf Muslihin , Heri; Loita , Aini; Nugraha, Dadan (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
Simple movements such as pompom stringing have significant benefits in supporting the growth and development of early childhood, particularly in terms of fine motor skills. This activity not only provides an enjoyable experience for children, but also contributes to improved eye-hand coordination and the ability to control and direct fine movements accurately. This study aims to examine the effect of pompom stringing activities on improving fine motor skills in 4-5-year-old children at TK Perwari 1 in Tasikmalaya City. The study employs the Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects consisted of 12 children selected based on age criteria and the need to improve fine motor skills. Data collection techniques were conducted through observation and documentation during the activity process. The results of the study showed a significant improvement in five main aspects of fine motor skills, namely eye-hand coordination, finger and hand muscle strength, precision and movement control, speed, and endurance. The children also demonstrated active participation and high enthusiasm during the pompom crafting activity. These findings indicate that the pompom crafting activity is effective in enhancing the fine motor skill development of young children and can be implemented as part of a fun and meaningful learning strategy in early childhood education settings